A lithium-ion battery

CN123018080APending Publication Date: 2026-10-30BASF BATTERY MATERIALS SUZHOU
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611208917.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]基于此,本发明的目的在于提供一种锂离子电池,以解决现有技术中锂离子电池难以在保证首效发挥的同时,兼顾高温循环性能以及高温存储后容量、阻抗和产气量要求的问题

Benefits of technology

[0042]本发明的锂离子电池,采用结构式1所示的化合物作为第一添加剂,碳酸丙烯酯作为有机溶剂,并限定了第一添加剂的质量百分含量a、碳酸丙烯酯的质量百分含量b和正极集流体中导电涂层的厚度c满足1.5≤b/5a≤10,0.2≤c/a≤10,且0.01≤a≤2,0.1≤b≤35,0.1≤c≤5时,能够实现较高的首次库伦效率,同时兼顾高温循环性能和高温存储后的综合表现,包括但不限于高的容量保持率、低的阻抗增长率以及低的产气量。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_10
    Figure SMS_10
  • Figure SMS_11
    Figure SMS_11
  • Figure SMS_12
    Figure SMS_12
Patent Text Reader

Abstract

The application relates to the technical field of batteries, in particular to a lithium ion battery. The lithium ion battery comprises a positive electrode, a negative electrode, an electrolyte and a diaphragm; the positive electrode comprises a positive electrode current collector, the positive electrode current collector comprises a conductive coating layer, the thickness of the conductive coating layer is c microns, and 0.1<=c<=5; the electrolyte comprises a lithium salt, a first additive and propylene carbonate; the first additive comprises a compound shown in structural formula 1; the mass percentage content of the first additive is a% based on the mass of the electrolyte, and the mass percentage content of the propylene carbonate is b%; the lithium ion battery satisfies 1.5<=b / 5a<=10, 0.2<=c / a<=10, 0.01<=a<=2 and 0.1<=b<=35. The lithium ion battery provided in the application can realize high initial coulomb efficiency, and meanwhile, the high-temperature cycle performance and the comprehensive performance after high-temperature storage are considered, including but not limited to high capacity retention rate, low impedance growth rate and low gas production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of battery technology, and more specifically to a lithium-ion battery. Background Technology

[0002] With the explosive growth of the new energy industry, lithium-ion batteries have been widely applied in electric vehicles, large-scale energy storage, and consumer products such as smartphones and laptops. The market is placing increasingly higher demands on battery safety, wide-temperature range operation, energy density, and cycle life. On the one hand, users seek high energy density and long cycle life; on the other hand, densely packed or close-range applications place stringent requirements on battery thermal stability. With the implementation and updates of a series of mandatory standards, such as the "Safety Technical Specification for Lithium-ion Batteries for Electric Bicycles" (GB 43854-2024), the industry entry threshold has significantly increased. This means that batteries must maintain extremely high structural stability at high temperatures. Therefore, while ensuring sufficient energy density and lifespan, further improving the high-temperature performance of batteries, including but not limited to improving capacity retention and reducing gas production during high-temperature storage and cycling, has become an urgent focus.

[0003] Propylene carbonate (PC), as a cyclic carbonate solvent with high dielectric constant, relatively low viscosity, and wide temperature range, has a strong ability to dissolve lithium salts. Its addition can improve low-temperature fluidity to some extent and suppress the crystallization tendency of ethylene carbonate (EC) at low temperatures. Simultaneously, its excellent thermal stability further consolidates the liquid-phase stability of the electrolyte at high temperatures. However, due to the risk of co-intercalation with graphite, it has limitations in completely replacing EC as the main solvent. Patent CN115528302A mentions an aromatic compound that can effectively achieve the desired effect when PC is used as the main solvent, reducing the concentration of lithium salts in the lithium salt. + Reversible insertion and extraction within graphite, when used in conjunction with a second additive, can improve cycle performance, but the impact on battery performance and safety after high-temperature storage is not mentioned. Patent CN118412536A mentions an additive combination containing cyclic disiloxane compounds that can improve gas expansion after high-temperature storage, DC internal resistance at room temperature, and high-temperature cycle capacity retention, but it does not mention the impact on battery energy density utilization or impedance growth changes after cycling or storage; these indicators are directly related to the overall battery performance and lifespan. Patent CN120565813A discloses a battery cell that mentions an electrolyte containing cyclic carbonate solvents including PC, and that when the thickness of the single-sided positive electrode conductive layer is within a certain range, it can balance the battery cell's energy density, fast charging capability, and reliability, but it also does not mention how the battery performs after a period of high-temperature storage.

[0004] Therefore, a suitable solution is needed that can ensure the energy density of the battery, such as a high initial efficiency, and can still achieve the expected performance under high temperature conditions, whether after cycling or after a period of storage, including but not limited to a high capacity retention and recovery rate, reduced impedance growth rate and gas production. Summary of the Invention

[0005] Based on this, the purpose of the present invention is to provide a lithium-ion battery that solves the problem in the prior art that lithium-ion batteries are difficult to ensure initial efficiency while also taking into account high-temperature cycle performance and the requirements for capacity, impedance and gas production after high-temperature storage.

[0006] The present invention adopts the following technical solution: A lithium-ion battery includes a positive electrode, a negative electrode, an electrolyte, and a separator; the positive electrode includes a positive electrode current collector, the positive electrode current collector includes a conductive coating, the thickness of the conductive coating is c µm, and 0.1≤c≤5; The electrolyte comprises a lithium salt, a first additive, and propylene carbonate; the first additive comprises a compound shown in structural formula 1. Structural Formula 1, R1 and R2 are each independently selected from substituted or unsubstituted C1~C12 alkyl, substituted or unsubstituted C2~C12 alkenyl, substituted or unsubstituted C2~C12 alkynyl, substituted or unsubstituted C3~C12 cycloalkyl, wherein when R1 and R2 are substituted, the substituent is halogen; x is an integer from 3 to 6. Based on the mass of the electrolyte, the mass percentage of the first additive is a%, and the mass percentage of the propylene carbonate is b%. The lithium-ion battery satisfies the following conditions: 1.5≤b / 5a≤10, 0.2≤c / a≤10, and 0.01≤a≤2, 0.1≤b≤35.

[0007] The lithium-ion battery provided in this invention uses the compound shown in structural formula 1 as the first additive and propylene carbonate as the organic solvent. The content of the compound shown in structural formula 1, the content of propylene carbonate, and the thickness of the conductive coating in the positive electrode current collector are limited. Through extensive experiments, the inventors discovered that when the mass percentage content a of the first additive, the mass percentage content b of propylene carbonate, and the thickness c of the conductive coating satisfy 1.5≤b / 5a≤10, 0.2≤c / a≤10, and 0.01≤a≤2, 0.1≤b≤35, and 0.1≤c≤5, a high initial coulombic efficiency can be achieved, while also considering high-temperature cycling performance and overall performance after high-temperature storage, including but not limited to high capacity retention, low impedance growth rate, and low gas production. The reasons are presumably twofold: firstly, introducing the compound shown in Formula 1 as an additive can preferentially form an SEI film rich in organosilicon polymers on the graphite anode surface, thereby stabilizing the interface and reducing the risk of co-intercalation of propylene carbonate (PC) with graphite; secondly, a suitable coating thickness can help guide the first additive to decompose uniformly at the cathode to form a high-quality and stable interface film, maximizing its utilization. Since the cathode current collector itself is easily corroded and dissolved by HF (such as LiPF6 hydrolysis products) in the electrolyte, a suitable coating thickness acts as a physical barrier to completely cover the current collector, effectively inhibiting the dissolution of metal ions caused by current collector corrosion, preventing dissolved impurities from disrupting the film-forming pathway of the first additive, and a suitable thickness means that the active sites are moderate, enabling the mild and controllable decomposition of the compound shown in Formula 1, slowing down its rapid consumption, extending the shelf life of the additive, and ensuring a stable supply of film-forming precursors. Furthermore, the SEI film grows, expands, breaks down, and rebuilds during charge-discharge cycles, continuously consuming additives. A coating of appropriate thickness ensures that its pore structure can accommodate the growth space of the SEI film, preventing film breakage. The more stable the SEI, the less additive is consumed, and the higher the utilization rate of the additives, which helps to extend the cycle life. Through the synergistic effect of the above components, a lithium-ion battery that balances high-temperature cycle performance and high-temperature storage is finally obtained.

[0008] In some embodiments, when the addition amounts of the first additive and propylene carbonate (PC) satisfy 1.5 ≤ b / 5a ≤ 10, high-temperature performance can be further improved, including but not limited to suppressing gas generation after high-temperature storage, improving high-temperature cycle capacity retention, and reducing impedance growth rate. When the value of the relationship b / 5a is greater than 10, the effect of improving high-temperature performance is limited, especially in suppressing gas generation and cycle capacity, and may even degrade the negative electrode interface, causing a decrease in capacity retention, gas generation at high temperatures, and shortening battery life; when the value of the relationship b / 5a is less than 1.5, the relative addition amount of the first additive is too large, which may degrade the initial impedance and affect low-temperature and rate performance.

[0009] When the thickness of the conductive coating and the amount of the first additive satisfy 0.2 ≤ c / a ≤ 10, the film-forming effect of the first additive can be maximized, achieving a better effect in improving high-temperature performance. When the value of c / a is less than 0.2, it may actually degrade the impedance. When the value of c / a is greater than 10, the improvement in high-temperature performance, especially in suppressing gas generation, is limited.

[0010] Preferably, the mass percentage a of the compound represented by structural formula 1, the mass percentage b of propylene carbonate, and the thickness c of the conductive coating satisfy 2 ≤ b / 5a ≤ 6.5 and 1.5 ≤ c / a ≤ 6.

[0011] In some embodiments, when the mass percentage a% of the first additive is too high, the resulting SEI film is too thick, leading to increased interfacial impedance and affecting lithium-ion transport and battery rate performance. When the content a% of the first additive is too low, a dense and effective SEI film cannot be formed, which is insufficient to suppress the co-intercalation of propylene carbonate (PC) and graphite, resulting in graphite peeling and capacity decay. Specifically, the mass percentage a% of the first additive is 0.01%, 0.03%, 0.05%, 0.08%, 0.1%, 0.12%, 0.15%, 0.18%, 0.2%, 0.3%, 0.5%, 0.6%, 0.7%, 1.0%, 1.2%, 1.5%, 1.8%, 2.0%, or any combination of these values. Preferably, the mass percentage a% of the first additive satisfies 0.2 ≤ a ≤ 0.6. Within this range, the first additive can generate a moderately thick and dense SEI film on the negative electrode, thereby inhibiting the co-intercalation of propylene carbonate (PC) and graphite, improving lithium-ion transport, battery rate performance, and suppressing battery capacity decay.

[0012] In some embodiments, when the mass percentage b% of propylene carbonate is too small, the low-temperature fluidity of the electrolyte is not sufficiently improved, which will exacerbate ion transport resistance, leading to a sharp drop in battery capacity at low temperatures, an increased risk of lithium plating, and a severe deterioration in rate performance. When the mass percentage b% of propylene carbonate is too large, the risk of co-intercalation with graphite increases significantly, which will severely damage the graphite structure, resulting in a decrease in capacity retention, an increase in impedance growth rate, and a significant increase in gas production during high-temperature cycling and storage. Specifically, the mass percentage b% of propylene carbonate is 0.01%, 0.05%, 0.1%, 0.5%, 1.0%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 25%, 28%, 30%, 32%, 35%, or any combination of these values; preferably, the mass percentage b% of propylene carbonate satisfies 3 ≤ b ≤ 20. Within this range, the electrolyte exhibits both good low-temperature fluidity and graphite structural stability, effectively reducing ion transport resistance, improving low-temperature rate performance and capacity retention, while suppressing co-intercalation reactions, ensuring that capacity retention, impedance growth, and gas production are all within a controllable range during high-temperature cycling and storage.

[0013] In some embodiments, when the thickness c of the conductive coating is too thin, the current collector is not completely covered, resulting in severe metal side reactions that preempt the reaction priority of the first additive. This causes a large amount of the first additive to be consumed by useless side reactions, leaving very little actually used for SEI film formation. Secondly, while a thin coating means that the first additive can quickly reach the interface due to its short diffusion path and form a film quickly, it also means that it is prone to explosive decomposition, which may result in a thick, loose, and high-resistance SEI. When the thickness c of the conductive coating is too thick, the overall carbon specific surface area increases, resulting in too many surface defect sites. The first additive is largely catalyzed and consumed at these defect sites. When the first additive is depleted prematurely, it will lead to incomplete film formation and increased interfacial polarization. Specifically, the thickness c µm of the conductive coating is 0.1 µm, 0.2 µm, 0.4 µm, 0.6 µm, 0.8 µm, 1.0 µm, 1.2 µm, 1.4 µm, 1.6 µm, 1.8 µm, 2.0 µm, 2.2 µm, 2.4 µm, 2.6 µm, 2.8 µm, 3.0 µm, 3.2 µm, 3.4 µm, 3.6 µm, 3.8 µm, 4.0 µm, 4.2 µm, 4.5 µm, 4.6 µm, 4.8 µm, 5.0 µm, or any combination of these values; preferably, the thickness c µm of the conductive coating satisfies 1 ≤ c ≤ 3. Within this range, the conductive coating can effectively coat the current collector, minimizing the consumption of the first additive and enabling it to form a dense and effective SEI film on the negative electrode. This fundamentally suppresses the side reactions that intensify at high temperatures, achieving low attenuation, low impedance, and low gas production under high-temperature conditions, thus ensuring the battery's high-temperature lifespan and safety reliability.

[0014] In some embodiments, X in the first additive is 3, 4, 5, or 6; the halogen substituent is fluorine. Preferably, the first additive comprises one or more of the following compounds: .

[0015] In some embodiments, the lithium salt is selected from LiPF6, LiBOB, LiDFOB, LiPO2F2, LiBF4, LiSbF6, LiAsF6, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiC(SO2CF3)3, LiN(SO2F)2, LiClO4, LiAlCl4, LiCF3SO3, Li2B 10 Cl 10 At least one of the following: lithium salts of lower aliphatic carboxylic acids.

[0016] In some embodiments, the lithium salt content is 5% to 20% by mass, based on 100% of the electrolyte. Specifically, the lithium salt content, based on 100% of the electrolyte, can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, or any combination thereof. In a preferred embodiment, the lithium salt content is 8% to 15% by mass, based on 100% of the electrolyte.

[0017] In some embodiments, the electrolyte further includes auxiliary additives selected from at least one of cyclic carbonate compounds, cyclic sulfate compounds, sulfonyl lactone compounds, phosphate compounds, borate ester compounds, and nitrile compounds.

[0018] Based on the total mass of the electrolyte (100%), the content of the auxiliary additive is 0.01% to 30%. Specifically, the content of the auxiliary additive is within the range of 0.01%, 0.05%, 0.1%, 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3%, 3.5%, 4.5%, 5%, 5.5%, 6.0%, 6.5%, 7.0%, 7.5%, 8.0%, 8.5%, 9.0%, 10%, 13%, 15%, 17%, 20%, 23%, 25%, 28%, 30%, or any combination of both.

[0019] In some embodiments, the cyclic carbonate compound is selected from at least one of vinylene carbonate, ethylene ethylene carbonate, methylene carbonate, fluoroethylene carbonate, trifluoromethyl ethylene carbonate, difluoroethylene carbonate, or the compound represented by structural formula 2 below: Structural Formula 2, In structural formula 2, R 21 R 22 R 23 R 24 R 25 R 26 Each is independently selected from one of the following: hydrogen atom, halogen atom, or C1-C5 group.

[0020] The compound shown in structural formula 2 includes at least one of the compounds shown in compounds 2-1 to 2-6 below: .

[0021] In some embodiments, the cyclic sulfate compound is selected from vinyl sulfate, 4-methylvinyl sulfate, propylene sulfate, etc. , , At least one of them.

[0022] In some embodiments, the sulfonyl lactone compound is selected from 1,3-propanesulfonyl lactone, 1,4-butanesulfonyl lactone, propenyl-1,3-sulfonyl lactone, etc. At least one of them.

[0023] In some embodiments, the phosphate ester compounds include saturated phosphate ester compounds and unsaturated phosphate ester compounds, wherein the saturated phosphate ester compounds include tris(trimethylsilane) phosphate esters, and the unsaturated phosphate ester compounds include compounds represented by structural formula 3 below: Structural Formula 3 In structural formula 3, R 31 R 32 R 33 Each is independently selected from C1-C5 saturated hydrocarbon groups, unsaturated hydrocarbon groups, halohydrocarbon groups, and -Si(C m H 2m+1 )3, m is a natural number from 1 to 3, and R 31 R 32 R 33 At least one of them is an unsaturated hydrocarbon group.

[0024] In some preferred embodiments, the compound represented by structural formula 3 includes at least one of the following: triargyl phosphate, diallyl methyl phosphate, diallyl ethyl phosphate, diallyl propyl phosphate, diallyl trifluoromethyl phosphate, diallyl-2,2,2-trifluoroethyl phosphate, diallyl-3,3,3-trifluoropropyl phosphate, diallyl hexafluoroisopropyl phosphate, triallyl phosphate, diallyl methyl phosphate, diallyl ethyl phosphate, diallyl propyl phosphate, diallyl trifluoromethyl phosphate, diallyl-2,2,2-trifluoroethyl phosphate, diallyl-3,3,3-trifluoropropyl phosphate, and diallyl hexafluoroisopropyl phosphate.

[0025] In some embodiments, the borate ester compounds include tris(trimethylsilane)borate and tris(triethylsilane)borate.

[0026] In some embodiments, the nitrile compound includes at least one selected from succinic acid, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrionitrile, adiponitrile, heptanonitrile, octanilide, nonadionitrile, and sebaconitrile.

[0027] In some embodiments, the positive current collector is selected from a metallic material that can conduct electrons; preferably, the positive current collector includes at least one of Al, Ni, tin, copper, and stainless steel; in a more preferred embodiment, the positive current collector is selected from aluminum foil.

[0028] In some embodiments, the positive electrode includes a positive electrode material layer, which is obtained by blending a positive electrode active material, a positive electrode binder, and a positive electrode conductive agent.

[0029] The positive electrode active material is selected from at least one of ternary materials, phosphate materials, lithium cobalt oxide materials, lithium-rich manganese materials, or lithium nickel manganese oxide materials. In some preferred embodiments, the ternary material comprises Li q Ni x Co y M 1-x-y O 2-g R g Li materials or surfaces with a coating layer q Ni x Co y M 1-x-y O 2-g R g At least one of the materials, wherein 0.9≤q≤1.2, 0.01≤x≤0.96, y>0, 1-xy>0, 0≤g≤1, M includes one or two of Mn and Al, and zero or one or more of Sr, Mg, Ti, Ca, Zr, Zn, Si, Fe, B, Ga, Cr, W, V, Nb, Ce, and R includes one or more of N, F, S and Cl.

[0030] In some preferred embodiments, the phosphate material includes materials with the molecular formula Li. r Mn α Fe β A 1-α-β PO 4-n G n Li materials or surfaces with a coating layer r Mn α Fe β A 1-α-β PO 4-n G n At least one of the materials, wherein 0.9≤r≤1.1, 0≤α≤0.8, 0.2≤β≤1, 0≤n≤0.1, A is selected from one or more of Ti, Mg, V, Cr, Zr, Nb, Zn, Al, Na, K, Mo, W, Ni, Co, Ga, Sn, Sb, Ge and W, and G includes one or more of N, F, S and Cl.

[0031] In some preferred embodiments, the lithium cobalt oxide material includes lithium cobalt oxide or lithium cobalt oxide doped and / or coated with any one or more elements selected from Ni, Mn, Mg, Al, Zr, W, F, B, Cr, Mo and rare earth elements.

[0032] In some preferred embodiments, the lithium nickel manganese oxide material comprises LiNi x' L' y’ Mn (2-x'-y') O4, or LiNi with a coating layer on its surface x' L' y’ Mn (2-x'-y') At least one of the O4 materials, 0.3≤x'≤0.6, 0.01≤y'≤0.2, and L' is selected from one or more of Co, Al, Sr, Mg, Ti, Ca, Zr, Zn, Si and Fe.

[0033] In a more preferred embodiment, the positive electrode active material may include LiCoO2, LiFePO4, or LiFe 0.4 Mn 0.6 PO4, LiMn2O4, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.7 Co 0.1 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.8 Co 0.15 Al 0.05 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2, LiNi 0.5 Co 0.2 Mn 0.2 Al 0.1 O2, LiNi 0.5 Co 0.2 Al 0.3 One or more of O2.

[0034] In some embodiments, the mass percentage of the positive electrode binder is 0.5% to 3%, based on the total mass of the positive electrode material layer being 100%.

[0035] In some embodiments, the positive electrode binder includes at least one of polyvinylidene fluoride, copolymers of polyvinylidene fluoride, polytetrafluoroethylene, copolymers of polyvinylidene fluoride-hexafluoropropylene, copolymers of tetrafluoroethylene-hexafluoropropylene, copolymers of tetrafluoroethylene-perfluoroalkyl vinyl ethers, copolymers of ethylene-tetrafluoroethylene, copolymers of polyvinylidene fluoride-tetrafluoroethylene, copolymers of polyvinylidene fluoride-trifluoroethylene, copolymers of polyvinylidene fluoride-trichloroethylene, copolymers of polyvinylidene fluoride-fluorinated vinylidene ether, copolymers of polyvinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, thermoplastic resins such as polyethylene and polypropylene, acrylic resins, and styrene-butadiene rubber.

[0036] In some embodiments, the positive electrode conductive agent includes one or more of carbon nanotubes, SP, and graphite powder. More preferably, the conductive agent is carbon nanotubes.

[0037] In some embodiments, the negative electrode further includes a negative electrode current collector and a negative electrode material layer disposed on the surface of the negative electrode current collector. The material of the negative electrode current collector may be the same as that of the positive electrode current collector, and will not be described in detail here.

[0038] In some embodiments, the negative electrode material layer is obtained by blending a negative electrode active material, a negative electrode binder, and a negative electrode conductive agent. The negative electrode active material is selected from one or more of silicon-based negative electrodes and carbon-based negative electrodes. The carbon-based negative electrode includes, but is not limited to, graphite, hard carbon, soft carbon, graphene, and mesophase carbon microspheres.

[0039] The negative electrode binder and negative electrode conductive agent can be the same as the positive electrode binder and positive electrode conductive agent, respectively, and will not be described in detail here.

[0040] In some embodiments, the battery further includes a separator located between the positive electrode and the negative electrode.

[0041] The diaphragm can be a conventional diaphragm, such as a ceramic diaphragm, a polymer diaphragm, a non-woven fabric, or an inorganic-organic composite diaphragm, including but not limited to single-layer PP (polypropylene), single-layer PE (polyethylene), double-layer PP / PE, double-layer PP / PP, and triple-layer PP / PE / PP diaphragms.

[0042] The lithium-ion battery of the present invention uses the compound shown in structural formula 1 as the first additive and propylene carbonate as the organic solvent. When the mass percentage content a of the first additive, the mass percentage content b of propylene carbonate, and the thickness c of the conductive coating in the positive electrode current collector are limited to satisfy 1.5≤b / 5a≤10, 0.2≤c / a≤10, and 0.01≤a≤2, 0.1≤b≤35, and 0.1≤c≤5, it can achieve a high initial coulombic efficiency, while taking into account the high-temperature cycling performance and the comprehensive performance after high-temperature storage, including but not limited to high capacity retention, low impedance growth rate, and low gas production. Detailed Implementation

[0043] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of the present invention, and not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the protection scope of the present invention.

[0044] Example 1 This embodiment uses the preparation of a lithium-ion battery as an example to illustrate the present invention, including the following operation steps: 1. Preparation of positive electrode sheet Conductive carbon black Super-P and binder polyvinylidene fluoride (PVDF) were mixed at a mass ratio of 90:10, and an appropriate amount of N-methyl-2-pyrrolidone (NMP) was added. The mixture was thoroughly stirred and dispersed to obtain a uniform conductive coating slurry. The conductive slurry was uniformly coated onto the opposite surfaces of an aluminum foil (positive electrode current collector) to form an extremely thin conductive undercoat. The foil was then dried in an oven to remove the NMP solvent. The positive electrode active material LiNi... 0.8 Co 0.1 Mn 0.1 O2, conductive carbon black Super-P, and binder PVDF are mixed in a mass ratio of 94:3:3, and an appropriate amount of NMP is added. The mixture is then dispersed at high speed to prepare a positive electrode slurry. The positive electrode slurry is uniformly coated onto a dried conductive coating (also coated on both sides of an aluminum foil). After drying, rolling, and vacuum drying, aluminum leads are welded on using an ultrasonic welder to obtain the positive electrode sheet. The thickness of the conductive coating is 1 μm.

[0045] 2. Preparation of negative electrode sheet Artificial graphite, conductive carbon black Super-P, styrene-butadiene rubber (SBR), and carboxymethyl cellulose (CMC) were mixed in a mass ratio of 95.2:1.0:2.4:1.4 to obtain a negative electrode slurry. The slurry was then coated onto opposite surfaces of a copper foil, dried, calendered, and vacuum dried, and finally had nickel leads welded on using an ultrasonic welder to obtain the negative electrode sheet.

[0046] 3. Preparation of electrolyte Propylene carbonate (PC), ethylene carbonate (EC), and ethyl methyl carbonate (EMC) were mixed, compound 1-1 was added, and then lithium hexafluorophosphate (LiPF6) was added to a molar concentration of 1 mol / L. Based on the mass of the electrolyte, the content of propylene carbonate was 6.5%, and the content of compound 1-1 (the first additive) was 0.2%.

[0047] 4. Lithium-ion cell manufacturing The prepared positive electrode and the prepared negative electrode are assembled into a stacked battery cell.

[0048] 5. Electrolyte injection and formation of battery cells In a glove box with the dew point controlled below -40°C, the electrolyte prepared above was injected into the cell, vacuum sealed, and left to stand for 72 hours. Then, the first charge was performed according to the following steps: 0.05C constant current charging for 180 minutes, 0.1C constant current charging for 120 minutes, 0.2C constant current charging for 120 minutes, followed by a second vacuum sealing, and then a full charge at 0.2C (100% SOC). After resting at room temperature for 72 hours, a full discharge at 0.2C (0% SOC) was performed.

[0049] Examples 2-23 and Comparative Examples 1-15 Examples 2-23 and Comparative Examples 1-15 are basically the same as Example 1, except for the type and content of the first additive, the content of propylene carbonate, the thickness of the positive electrode conductive coating, the type and content of the auxiliary additives, and the values ​​of the relationships b / 5a and c / a.

[0050] Performance testing The lithium-ion batteries prepared above were subjected to the following performance tests: 1. Capacitance retention and impedance growth rate after 500 cycles at 45℃ The lithium-ion battery was placed in a constant-temperature oven at 45°C and charged to 4.2V with a constant current and constant voltage of 1C, with a cutoff current of 0.05C. Then, it was discharged to 3.0V with a constant current of 1C. This cycle was repeated 500 times, and the discharge capacity of the first and last cycles was recorded. Before the start of the cycle (after the first charge to full capacity) and after the 500 cycles (after the last discharge to 3.0V, and then charged to 4.2V with a constant current and constant voltage of 1C), the AC internal resistance of the battery at a frequency of 1kHz was measured using the AC impedance method (or the ohmic internal resistance at a specific frequency was measured according to industry standards). The initial internal resistance value R0 and the internal resistance value R1 after 500 cycles were recorded.

[0051] Calculate the high-temperature cycling capacity retention and impedance growth rate using the following formula: Capacity retention rate (%) = last discharge capacity / first discharge capacity × 100%.

[0052] Impedance growth rate (%) = (R1-R0) / R0×100%.

[0053] Where R0 is the initial fully charged AC internal resistance before the cycle, and R1 is the fully charged AC internal resistance after 500 cycles.

[0054] 2. Capacity retention rate after 30 days of storage at 60℃ A lithium-ion battery was charged to 4.2V at room temperature (25℃±2℃) using a constant current and constant voltage of 1C, with a cutoff current of 0.05C. It was then discharged to 3.0V using a constant current of 1C, and the discharge capacity C0 (initial capacity) was recorded. The battery was then charged again to 4.2V using a constant current and constant voltage of 1C, with a cutoff current of 0.05C, bringing it to a fully charged state. The fully charged battery was stored in an oven at a constant temperature of 60℃ for 30 days. After storage, it was removed and placed at room temperature (25℃±2℃) for 2 hours, then discharged to 3.0V using a constant current of 1C, and the discharge capacity C1 was recorded.

[0055] Calculate the high-temperature storage capacity retention rate using the following formula: Capacity retention rate (%) = C1 / C0 × 100%.

[0056] Where C0 is the initial discharge capacity before storage, and C1 is the discharge capacity after 30 days of storage.

[0057] 4. Gas production rate after 30 days of storage at 60℃ The lithium-ion battery was charged to 4.2V at a constant current and voltage of 1C with a cutoff current of 0.05C at room temperature (25℃±2℃) until it was fully charged. The initial volume V0 (in mL) of the battery in the fully charged state was measured using the Archimedes displacement method (or a high-precision gas volume measuring device). The fully charged battery was then stored in an oven at a constant temperature of 60℃ for 30 days. After storage, the battery was removed and placed at room temperature (25℃±2℃) for 2 hours, and the battery volume V1 was measured again using the same method.

[0058] Calculate the gas production rate of high-temperature storage using the following formula: Gas production rate (%) = (V1-V0) / V0×100%.

[0059] Where V0 is the initial fully charged battery volume before storage, and V1 is the battery volume after 30 days of storage.

[0060] Test Results Table 1 shows the parameters required for preparing lithium-ion batteries in Examples 1-15 and Comparative Examples 1-15. The differences between Examples 2-15 and Comparative Examples 1-15 and Example 1 lie in the relevant parameters listed in Table 1; all other parameters are the same as in Example 1. Specifically, the differences are: the content of the first additive (compound 1-1), the content of propylene carbonate, the thickness of the positive electrode conductive coating, and the values ​​of the relationships b / 5a and c / a. The test results are shown in Table 1.

[0061] Table 1 Note: "-" in the table indicates that the item does not exist.

[0062] As shown in the test results in Table 1, the lithium-ion battery provided by this invention uses the compound shown in structural formula 1 as the first additive and propylene carbonate as the organic solvent. It is determined that when the mass percentage of the first additive (a%), the mass percentage of propylene carbonate (b%), and the thickness of the conductive coating (c µm) satisfy 1.5 ≤ b / 5a ≤ 10, 0.2 ≤ c / a ≤ 10, and 0.01 ≤ a ≤ 2, 0.1 ≤ b ≤ 35, and 0.1 ≤ c ≤ 5, the battery can achieve a high initial coulombic efficiency while also considering high-temperature cycling performance and overall performance after high-temperature storage, including but not limited to high capacity retention, low impedance growth rate, and low gas production. Ultimately, a lithium-ion battery that balances high-temperature cycling performance and high-temperature storage is obtained.

[0063] The test results of Example 1 and Comparative Examples 1-15 show that when the mass percentage content a of the first additive, the mass percentage content b of propylene carbonate, the thickness c of the conductive coating, or any one or more of the values ​​of the relationship b / 5a and c / a in the lithium-ion battery do not meet the specified range, the coating of the positive electrode cannot effectively inhibit the dissolution of metal ions caused by the corrosion of the current collector, which destroys the film formation path of the first additive. As a result, the first additive cannot form an SEI film rich in organosilicon polymer on the negative electrode, cannot reduce the risk of co-intercalation of propylene carbonate and graphite, and cannot simultaneously improve the high-temperature cycle performance and high-temperature storage performance of the lithium-ion battery.

[0064] When the mass percentage of the first additive (a), the mass percentage of propylene carbonate (b), and the thickness (c) of the conductive coating in a lithium-ion battery further satisfy 2≤b / 5a≤6.5, 1.5≤c / a≤6, and 0.2≤a≤0.6, 3≤b≤20, and 1≤c≤3, the conductive coating can effectively coat the current collector, minimizing the consumption of the first additive. This allows the additive to form a moderately thick and dense SEI film at the negative electrode, thereby suppressing the co-intercalation of propylene carbonate and graphite. This fundamentally inhibits the side reactions that intensify at high temperatures, achieving low attenuation, low impedance, and low gas production under high-temperature conditions. This ensures the high-temperature lifespan and safety reliability of the battery, improves lithium-ion transport, battery rate performance, and suppresses battery capacity decay.

[0065] Table 2 shows the performance test results of the lithium-ion batteries prepared in Examples 1 and 16-20. The difference between Examples 16-20 and Example 1 is the type of the first additive shown in Table 2. The other parameters and preparation steps are the same as those described in Example 1.

[0066] Table 2 As shown in Table 2, when the mass percentages of the first additive (a%), propylene carbonate (b%), and conductive coating (c µm) in the lithium-ion battery, and the values ​​of their relationships (b / 5a, c / a) satisfy the corresponding conditions, lithium-ion batteries that balance high-temperature cycle performance and high-temperature storage can be obtained by adding different types of first additives. This demonstrates that the battery system of the present invention is universally applicable to different types of first additives.

[0067] Table 3 shows the performance test results of the lithium-ion batteries prepared in Examples 1 and 21-23. The difference between Examples 21-23 and Example 1 is the type and content of the auxiliary additives shown in Table 3. The other parameters and preparation steps are the same as those described in Example 1.

[0068] Table 3 Note: "-" in the table indicates that the item is not present; "HTCN" represents 1,3,6-hexanetrionitrile; "SN" represents succinic anionyl; "TMSB" represents tri(trimethylsilyl) borate; "PS" represents 1,3-propanesulfonyl lactone.

[0069] As shown in Table 3, when the mass percentages of the first additive (a%), propylene carbonate (b%), and conductive coating (c µm) in the lithium-ion battery, and the values ​​of their relationships (b / 5a, c / a) satisfy the corresponding conditions, lithium-ion batteries that balance high-temperature cycle performance and high-temperature storage can be obtained by adding different types of auxiliary additives. This demonstrates that the battery system of the present invention is universally applicable to different types of auxiliary additives.

[0070] The present invention has been further described above with reference to specific embodiments. However, it should be understood that the specific description herein should not be construed as limiting the nature and scope of the present invention. Various modifications made to the above embodiments by those skilled in the art after reading this specification are all within the scope of protection of the present invention.

Claims

1. A lithium-ion battery, characterized in that, It includes a positive electrode, a negative electrode, an electrolyte, and a separator; the positive electrode includes a positive current collector, the positive current collector includes a conductive coating, the thickness of the conductive coating is c µm, and 0.1≤c≤5; The electrolyte comprises a lithium salt, a first additive, and propylene carbonate; the first additive comprises a compound shown in structural formula 1. Structural Formula 1, R1 and R2 are each independently selected from substituted or unsubstituted C1~C12 alkyl, substituted or unsubstituted C2~C12 alkenyl, substituted or unsubstituted C2~C12 alkynyl, substituted or unsubstituted C3~C12 cycloalkyl, wherein when R1 and R2 are substituted, the substituent is halogen; x is an integer from 3 to 6. Based on the mass of the electrolyte, the mass percentage of the first additive is a%, and the mass percentage of the propylene carbonate is b%. The lithium-ion battery satisfies the following conditions: 1.5≤b / 5a≤10, 0.2≤c / a≤10, and 0.01≤a≤2, 0.1≤b≤35.

2. The lithium-ion battery as described in claim 1, characterized in that, The lithium-ion battery satisfies the following conditions: 2≤b / 5a≤6.5, 1.5≤c / a≤6.

3. The lithium-ion battery as described in claim 1, characterized in that, The mass percentage a% of the first additive satisfies 0.2≤a≤0.

6.

4. The lithium-ion battery as described in claim 1, characterized in that, The mass percentage b% of propylene carbonate satisfies 3 ≤ b ≤ 20.

5. The lithium-ion battery as described in claim 1, characterized in that, The thickness c of the conductive coating satisfies 1≤c≤3.

6. The lithium-ion battery as described in claim 1, characterized in that, The first additive includes one or more of the following compounds: 。 7. The lithium-ion battery as described in claim 1, characterized in that, The lithium salt is selected from LiPF6, LiBOB, LiDFOB, LiPO2F2, LiBF4, LiSbF6, LiAsF6, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiC(SO2CF3)3, LiN(SO2F)2, LiClO4, LiAlCl4, LiCF3SO3, and Li2B. 10 Cl 10 At least one of the following: lithium salts of lower aliphatic carboxylic acids.

8. The lithium-ion battery as described in claim 1, characterized in that, The electrolyte also includes auxiliary additives, which are selected from at least one of cyclic carbonate compounds, cyclic sulfate compounds, sulfonyl lactone compounds, phosphate compounds, borate ester compounds, and nitrile compounds.

9. The lithium-ion battery as described in claim 8, characterized in that, Based on the total mass of the electrolyte as 100%, the content of the auxiliary additives is 0.01% to 30%.

10. The lithium-ion battery as described in claim 8, characterized in that, The cyclic carbonate compound is selected from at least one of vinylene carbonate, ethylene ethylene carbonate, methylene carbonate, fluoroethylene carbonate, trifluoromethyl ethylene carbonate, difluoroethylene carbonate, or the compound shown in structural formula 2 below: Structural Formula 2, In structural formula 2, R 21 R 22 R 23 R 24 R 25 R 26 Each is independently selected from one of the following: hydrogen atom, halogen atom, C1-C5 group; and / or, The cyclic sulfate compounds are selected from vinyl sulfate, 4-methylvinyl sulfate, propylene sulfate, etc. , , At least one of them; and / or, The sulfonyl lactone compounds are selected from 1,3-propanesulfonyl lactone, 1,4-butanesulfonyl lactone, propenyl-1,3-sulfonyl lactone, and others. At least one of them; and / or, The phosphate ester compounds include saturated phosphate ester compounds and unsaturated phosphate ester compounds, wherein the saturated phosphate ester compounds include tris(trimethylsilane) phosphate esters, and the unsaturated phosphate ester compounds include compounds represented by structural formula 3 below: Structural Formula 3 In structural formula 3, R 31 R 32 R 33 Each is independently selected from C1-C5 saturated hydrocarbon groups, unsaturated hydrocarbon groups, halohydrocarbon groups, and -Si(C m H 2m+1 )3, m is a natural number from 1 to 3, and R 31 R 32 R 33 At least one of them is an unsaturated hydrocarbon group; and / or, The borate ester compounds include tris(trimethylsilane)borate and tris(triethylsilane)borate; and / or, The nitrile compounds include at least one of butadionitrile, glutaronitrile, ethylene glycol bis(propionitrile) ether, hexanetrionitrile, adiponitrile, heptacyanide, octadionitrile, nonadionitrile, and sebaconitol.

Citation Information

Patent Citations

  • Electrolyte for lithium ion battery based on propylene carbonate and lithium ion battery

    CN115528302A

  • Lithium ion battery non-aqueous electrolyte additive composition for improving flatulence, impedance and high-temperature cycle performance and non-aqueous electrolyte thereof

    CN118412536A

  • Battery cell, battery device and electric device

    CN120565813A